Cepljenje proti gripi in pnevmokoku pri starostnikih v domovih starejših občanov - Petek Šter, Marija (Zdravstveno varstvo, 2008)
Background: Vaccination is one of the most important public health measures for the prevention and control of infectious diseases. Influenza vaccination is recommended for all nursing home residents, and pneumococcal vaccination for people over 65 years of age. In Slovenia, data on the influenza and pneumoccocal vaccination rates in elderly nursing home residents are not available. Objectives: To determine influenza and pneumococcal vaccine coverage in elderly nursing home residents and identify factors influencing the rate of immunization. Patients and methods: In a cross-sectional retrospective study, data for 2,040 elderly nursing home residents from 12 nursing homes in Slovenia were analysed. The source of data were paper patient records and nursing documentation. Results: There were 1,605 female (78.7%) and 435 male (21.3%) nursing home residents, aged 65 to 104 years. Theaverage age was 82.3 (SD 7.8 years). As many as 452 (22.2%) of them were completly independent in their activities of daily living (ADL), 383 (18.8%) were partially dependent, and 1,205 (59.0%) were either completely dependent or in need of 24-hour supervision. The rate of vaccination against influenza and against pneumococci in elderly nursing home residents was 69.1% and 4.3%, respectively. The influenza vaccination rate was dependent on the organisationof vaccination in nursing homes ( 2 =59.432, p<0.001), but was notinfluenced by the characteristics of the study population. Conclusions: Theinfluenza vaccination rate varied largely among the nursing homes. The highvaccination rate established in some nursing homes suggested that immunisation is possible in the majority of elderly nursing home residents.Promotion activities for pneumococcal vaccination should be itensified and should involve provision of free vaccine for all people over 65 of age.
Keywords: cepljenje; gripa; pnevmokoki; preventivna medicina; starostniki